Questions of Income and Expenditure in Renaissance Rome: a Case Study of Cardinal Francesco Armellini - Lowe, K. J. P. (Studies in church history, 1987)
In, a book of 1567 on the lives and actions of past popes and cardinals written by Girolamo Garimberto, in the section on avarice, is to be found this judgement on Cardinal Francesco Armellini (1470-1528). ‘He truly is to be considered rich who is content to live with what he has, while he who is unhappy with what he has accumulated may be considered poor; and measured in these terms one can say that Francesco Armellini was very poor indeed.’ Given his posthumous, and indeed his contemporary reputation, of which this passage is entirely typical, Francesco Armellini would appear to be an ideal figure through which to approach the general subject of the Church and wealth in this period.